DETERMINANTS OF IPO OVERSUBSCRIPTION ON ISLAMIC STOCKS: EVIDENCE FROM INDONESIA - Azwar Aulia Rasyad; Bayu Arie Fianto; Rogier Busser (Journal of Islamic Monetary Economics and Finance, 2022)
This study aims to investigate factors that affect IPO oversubscription on Islamic stocks. Using data of 202 IPOs indexed from Indonesia Sharia Stock Index, this study uses ordinary least squaresand quantile regression to test the formulated hypothesis from 2011 to 2020. This study finds that issue price and issue size negatively affect IPO oversubscription. Meanwhile, firm size and raw return positively affect IPO oversubscription. The findings of this study offer implications forcompanies especially related to go public subscription. This study can be reference for investors as well when engage in IPO related activities for Islamic stocks.